Plasmodesmata-mediated intercellular signaling during plant growth and development - Yadav, Shri Ram; Yan, Dawei; Sevilem, Iris; Helariutta, Ykä (Frontiers in Plant Science, 2014)
Plasmodesmata (PD) are cytoplasmic channels that connect neighboring cells for cell-to-cell communication. PD structure and function vary temporally and spatially to allow formation of symplastic domains during different stages of plant development. Reversible deposition of callose at PD plays an important role in controlling molecular trafficking through PD by regulating their size exclusion limit (SEL). Previously, we reported several semi-dominant mutants for CALLOSE SYNTHASE 3 (CALS3) gene, which overproduce callose at PD in Arabidopsis. By combining two of these mutations in a LexA-VP16-ER (XVE)-based estradiol inducible vector system, a tool known as the “icals3m system” was developed to temporally obstruct the symplastic connections in a specified spatial domain. The system has been successfully tested and used, in combination with other methods, to investigate the route for mobile signals such as the SHR protein, microRNA165/6, and cytokinins in Arabidopsis roots, and also to understand the role of symplastic domain formation during lateral root development. We envision that this tool may also be useful for identifying tissue-specific symplastic regulatory networks and to analyze symplastic movement of metabolites.